Regional Policy Against Poverty (example of Irkutsk region) - БелоусоваСветлана Владимировна (Journal of Economic Sociology, 2010)
Poverty is the current Russian problem which became mass and constant phenomenon during the reforms years. The author gives the review of quantitative and qualitative approaches towards poverty estimation. The focus is placed on macro-economic aspects of poverty analysis and ways to prevent it.